Pembelajaran materi operasi hitung bilangan pecahan pada siswa kelas VII MTs dengan menggunakan pendekatan saintifik berbantuan video - Titin Fatimah; Adi Nurjaman (IKIP Siliwangi, 2026)
The purpose of this research is to examine the scenarios and implementations of the responses of teachers and students, the difficulties faced by students in solving mathematical problem-solving tests, and the constraints experienced by teachers in learning using a video-assisted scientific approach. The research employs a qualitative descriptive method with both test and non-test instruments. The subjects of the research were 20 seventh-grade students from a Madrasah in Bandung Regency. The results indicated that the teacher's response was positive. The average pretest score of students was 34.5, which improved to an average posttest score of 73.5. Students responded positively, categorizing the learning outcomes as enjoyable, with an average questionnaire result of 3.51. Based on these results, it can be concluded that students understood the material. The difficulties faced by students are a small number of students who did not understand the concepts of questions related to operations with fractional numbers, leading to answers that did not correspond to what was requested in the questions. The constraints faced by teachers included the need for more time to teach and the necessity to sometimes replay videos so that students could thoroughly understand the material presented.